Fitness and Mating Compatibility of Spodoptera frugiperda (Lepidoptera: Noctuidae) Populations from Different Host Plant Species and Regions in Argentina - Murúa, María Gabriela (2008)
Two strains (corn and rice) of fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), have been identified that differ in their host plant preferences and performance. Although these strains have been shown to be partially reproductively incompatible, the geographic and host-related variability within them has received less attention. In the current study, fall armyworm larvae were collected from a variety of different hosts and from six provinces in Argentina. The following populations were established in the laboratory: Salta province (corn), Tucumán province (corn, alfalfa, soybean, wheat, and weeds), Santiago del Estero province (corn and alfalfa), Chaco province (weeds), Santa FÈprovince (corn), and Buenos Aires province (corn). The populations were characterized with respect to egg, larval, and pupal duration; pupal mass; adult longevity; sex ratio; number of spermatophores per female; preoviposition; oviposition and postoviposition period; number of eggs and egg masses per female; and egg viability. Small but significant differences were observed among the populations collected from different hosts within Tucumán province with respect to the duration of different life stages, pupal mass, and reproductive characteristics. Similarly, small but significant differences were observed among the populations collected from corn in different provinces. Reproductive compatibility studies also were conducted among the different fall armyworm corn populations, looking at the same reproductive parameters, as well as adult longevity. Fall armyworm populations from the north of the country showed no incompatibility among populations. However, indications of incompatibility were observed between the northern populations and a geographically distinct population from Buenos Aires.